Beyond feedback: introducing the 'engagement gap' in organizational energy management. Issue 3 (3rd April 2018) - Bull, Richard; Janda, Kathryn B.
ABSTRACT: This paper discusses socio-technical relationships between people, organizations and energy in workplaces. Inspired by Sherry Arnstein's ladder of citizen participation, it explores widening energy management beyond energy managers to other employees, introducing the idea of an 'engagement gap' to support a move beyond unidirectional forms of engagement ( e.g. feedback and nudging) to more socially interactive processes. Results are drawn from two projects researching energy practices in public authorities and retail organizations. The first project, 'GoodDeeds', collaboratively created an information and communication technology tool and explored participatory processes within a municipality. The second project, Working with Infrastructure, Creation of Knowledge, and Energy strategy Development (WICKED), explored energy management in retail companies. The paper uses a '4Cs' framework to articulate the influences of concerns, capacities and technical conditions within organizational communities . The results concur with previous research that energy management sits against a backdrop of competing organizational, institutional and political concerns. New data reveal discrepancies across organizations with regard to energy management capacities and technical metering conditions. The authors suggest employee engagement can be broadened by treating energy as a communal subject for discussion, negotiation and partnership. This objective moves beyond the 'information-deficit' approach intrinsic in the existing focus on analytics, dashboards and feedback.